Phenology of The Coffee Fruit Borer Beetle Hypothenemus hampei on Two Varieties of Coffee Plants - Praditya, Al Farriz Sandro; Rahardjo, Bambang Tri (University of Brawijaya, 2025)
Coffee (Coffea sp.) is one of the leading commodities in the Indonesian plantation sector. The low productivity of coffee plants can be caused by several factors, one of which is the loss caused by the Coffee Fruit Borer (CFB) Hypothenemus hampei Ferr (Coleoptera: Scolytidae). This research aims to study the flowering phenology of coffee plants and the influence of different plant varieties on the phenology of the CFB. The research was conducted using an exploratory survey method and laboratory analysis. Based on the results, the phenology of H. hampei in each phase has different characteristics, and it was found that there is overlap in the phenology phases of coffee fruit, which causes the life cycle of H. hampei to remain uninterrupted throughout the year. The highest population of H. hampei was found in the BGN 371 compared to the BP cultivar.